How Patients With Schizophrenia Use the Internet: Qualitative Study - Schrank, Beate; Sibitz, Ingrid; Unger, Annemarie; Amering, Michaela (JMIR Publications, 2010)
Background The Internet is an important source of health information for people with psychiatric conditions. Little is known about the way patients with schizophrenia use the Internet when it comes to issues related to their illness. Data on their specific needs, difficulties, and the consequences related to Internet use are lacking. Objective Our objective was to investigate the nature and subjective consequences of health-related Internet use among patients with schizophrenia. Methods In all, 26 individual semistructured interviews were conducted and analyzed qualitatively in groups of 4 until theoretical saturation was achieved. Results Study results suggest that the Internet is an influential source of illness-related information for patients with schizophrenia. Many aspects of their behavior around the Internet resemble those of individuals not afflicted by mental illness. Importantly, problems specific to patients with schizophrenia were stimulus overflow, an inability to deal with the abundance of information, difficulties with concentration, lack of energy, paranoid ideas, symptom provocation, and the need to distance themselves from illness-related topics as part of the recovery process. Internet information was subjectively perceived as having the potential to significantly change patients' attitudes toward medication and their relationships with doctors. Conclusions These findings provide insight into how individuals with schizophrenia handle illness-related Internet information. The data could contribute to the continuous development of Internet-based interventions and offer novel approaches to optimizing traditional treatment options.